Analisis Deiksis Dalam Cerita Pendek Rembulan di Mata Ibu dan Sepotong Cinta Dalam Diam Karya Asma Nadia - Sinta Ukhta Amalia; Laela Cahyani Rosyid; Sayidah Luthfi Nur Mukaromah; Fimahya Syafira Fiddinina; Adelia Nurul Fadilah; Asep Purwo Yudi Utomo; Yusro Edy Nugroho (STIKes Ibnu Sina Ajibarang, 2024)
Deixis is a pragmatic study that examines the relationship between language structure and the context of the situation in which it is used. The phenomenon of deixis can be found in everyday conversation in the form of verbal language as well as in literary works such as films or novels. In literary texts, deixis can pose an obstacle to understanding the text. The research entitled